PENGARUH CUSTOMER EXPERIENCE DAN CUSTOMER ENGAGEMENT TERHADAP CONTINUED ENGAGEMENT INTENTION MELALUI CUSTOMER SATISFACTION PADA PENGGUNA CHATBOT SABRINA BANK BRI REGIONAL OFFICE PADANG - Macelina Shally Ardias; Eri Besra; Alfitman (Journal Publicuho, 2025)
This research explores the impact of customer experience and engagement on the continued intention to use the service, highlighting the mediating role of customer satisfaction. The study was conducted among users of Chatbot Sabrina at Bank BRI Regional Office Padang, employing a quantitative approach with a survey of 210 respondents and analysis using structural equation modelling. Results show that both customer experience and engagement significantly enhance satisfaction, which subsequently drives the ongoing intention to use the chatbot. Customer satisfaction also mediates the relationship between experience, engagement, and continued use intention. Adopting the Service-Dominant Logic perspective, this research underscores the importance of value co-creation through customer-chatbot interaction as a critical source of competitive advantage. The findings emphasise the need for strategies focused on experience and engagement to boost satisfaction and loyalty among chatbot users, providing practical insights for financial institutions implementing this technology.